Psychological Stagnation and Avolition in the Poetry of Sylvia Plath - Suman, Shambhunath (Journal of Advanced Research in English & Education, 2025)
Sylvia Plath’s poetry is a profound exploration of the inner workings of the mind, particularly focusing on psychological stagnation and avolition—two states closely associated with depression. Her confes sional style brings to light the struggles of individuals immobilised by emotional paralysis and a lack of motivation. Plath’s poems, such as “Lady Lazarus,” “Tulips,” and “Mirror,” vividly depict the cyclical na ture of despair, the suffocating effects of inertia, and the yearning for transformation. Through her innovative use of imagery, fragmented structure, and recurring motifs of confinement, Plath encapsulates the lived experience of psychological stagnation. Simultaneously, her work interrogates the broader societal and gendered dimensions of mental illness, highlighting the pressures that contribute to avolition. By examining ten key aspects of these themes, this article demonstrates how Plath’s poetry not only represents but also critiques the conditions of psychological inertia. Drawing on recent scholarship, the discussion situates Plath’s work within the larger discourse on mental health, revealing its enduring relevance and therapeutic potential. Ultimately, Plath’s poetry emerges as a site of both suffering and resilience, offering insight into the complexities of depression and the struggle for agency.